1993
DOI: 10.1083/jcb.122.6.1301
|View full text |Cite
|
Sign up to set email alerts
|

Chaperonin-mediated folding of vertebrate actin-related protein and gamma-tubulin

Abstract: Abstract. The folding of actin and tubulin is mediated via interaction with a heteromeric toroidal complex (cytoplasmic chaperonin) that hydrolyzes ATP as part of the reaction whereby native proteins are ultimately released. Vertebrate actin-related protein (actin-RPV) (also termed centractin) and ~/-tubulin are two proteins that are distantly related to actin and tubulin, respectively: 3,-tubulin is exclusively located at the centrosome, while actin-RPV is conspicuously abundant at the same site. Here we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(108 citation statements)
references
References 37 publications
2
105
0
1
Order By: Relevance
“…Preparation of unfolded target proteins. Cloned cDNAs encoding the entire coding regions for ,B-actin (11), actinvertebrate actin-related protein (RPV) (26), (x- (47), 3-(48), and y-tubulin (50), TCP-1 (1), cyclin B (36), cap-binding protein (40), c-Myc (37), and p2lras (H-Ras) (25) were expressed as labeled polypeptides in E. coli BL21(DE3) by using pET vectors (43), and the labeled denatured proteins were purified from insoluble inclusion bodies as described before (16,17,31). The radiochemical and biochemical purity of each target protein was determined by analysis on SDS-polyacrylamide gels; this allowed an accurate estimation of specific radioactivity.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of unfolded target proteins. Cloned cDNAs encoding the entire coding regions for ,B-actin (11), actinvertebrate actin-related protein (RPV) (26), (x- (47), 3-(48), and y-tubulin (50), TCP-1 (1), cyclin B (36), cap-binding protein (40), c-Myc (37), and p2lras (H-Ras) (25) were expressed as labeled polypeptides in E. coli BL21(DE3) by using pET vectors (43), and the labeled denatured proteins were purified from insoluble inclusion bodies as described before (16,17,31). The radiochemical and biochemical purity of each target protein was determined by analysis on SDS-polyacrylamide gels; this allowed an accurate estimation of specific radioactivity.…”
Section: Methodsmentioning
confidence: 99%
“…UXT and co-factor D (Melki et al, 1993;Zhao et al, 2005;Cunningham and Kahn, 2008). Interestingly, co-factor D contains a series of HEAT sequence repeats, reminiscent of the HAT repeats found in HCA66, and silencing also results in spindle pole defects (Cunningham and Kahn, 2008).…”
Section: Journal Of Cell Science 122 (8)mentioning
confidence: 99%
“…Another striking difference between the two chaperonins is their different substrate specificity. In contrast to GroEL, which recognizes and assists folding of a broad range of non-native protein substrates, CCT has been demonstrated to facilitate folding of relatively few proteins: actin, tubulin, actin-and tubulin-related proteins, and luciferase (Gao et al, 1992;Frydman et al, 1992;Yaffe et al, 1992;Melki et al, 1993). It has been suggested that the subunits of the heterooligomeric cytosolic chaperonin may have evolved to achieve high specificity for cytoskeletal proteins.…”
mentioning
confidence: 99%